2006
DOI: 10.1079/bjn20051646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soya protein on serum lipid profile and lipoprotein concentrations in patients undergoing hypercholesterolaemic haemodialysis

Abstract: Clinical trials have shown that soya protein reduces the concentrations of some atherogenic lipids in subjects with normal renal function. The present study examined the effects of soya protein on serum lipid concentrations and lipoprotein metabolism in patients on hypercholesterolaemic haemodialysis. Twenty-six hypercholesterolaemic (total cholesterol $ 6·21 mmol/l) patients on haemodialysis were studied in a randomized, double-blind, placebo-controlled clinical trial. After a 4-week run-in phase, the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…Also, some research indicates that soy protein, when substituted for animal protein, decreases urinary protein levels in individuals with chronic renal disease and in patients with diabetes [167,168,169,170,171]. In addition, recent data suggest that soyfoods may also be useful for dialysis patients [172,173,174,175] and may have advantages for renal transplant patients [176]. …”
Section: Role Of Soy In Reducing Vegetarian Risk Of Chronic Diseasementioning
confidence: 99%
“…Also, some research indicates that soy protein, when substituted for animal protein, decreases urinary protein levels in individuals with chronic renal disease and in patients with diabetes [167,168,169,170,171]. In addition, recent data suggest that soyfoods may also be useful for dialysis patients [172,173,174,175] and may have advantages for renal transplant patients [176]. …”
Section: Role Of Soy In Reducing Vegetarian Risk Of Chronic Diseasementioning
confidence: 99%
“…However, the metaanalysis of several randomized controlled trials showed that soy protein and soy isoflavones have positive effects on the blood lipid profile [34,35]. In addition, the replacement of daily protein with soy protein for 8 to 12 weeks results in a reduction in total cholesterol, triglyceride, low-density lipoprotein, and Apo-lipoprotein B 100 (Apo-B 100) [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…A surprising finding, when comparing recent with earlier studies using soya protein, given as a total dietary substitute, is that even with partial substitution or just addition, remarkable cholesterol reductions occurred in severely hypercholesterolaemic individuals. This was particularly noticeable in two papers on patients on dialysis, in which 30 g/d soya protein were included in the diet as a drink (Chen et al 2005(Chen et al , 2006. A paper that has compared different daily soya protein intakes in hypercholesterolaemic individuals seems to indicate that increasing the intake above 30 g/d does not improve the response (Tonstad et al 2002).…”
Section: Discussionmentioning
confidence: 99%